THE MAJOR STAGES OF THE FORMATION - Valentyna Papushyna (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
For successful formation of aesthetic culture of students, the author of the article suggests the following stages of work: diagnostic and motivational, cognitive linguocultural, personality-oriented, activity-practical. There have been shown the methods of studying the basic aesthetic knowledge and interests of students, their next task-oriented development in practice. The article deals with personality-oriented activities, self-inclusive and creative forms of activities and other innovative methods of the development of linguocultural and art knowledge while working with literary texts during class and extracurricular hours, their judicious usage at all above mentioned stages. It has beed determined that the textbook and methodical manuals created in the course of emphasis on aesthetic knowledge direct students' activity and give clues in studying literature together with other art forms.